2017
DOI: 10.1063/1.4986048
|View full text |Cite
|
Sign up to set email alerts
|

True randomness from an incoherent source

Abstract: Quantum random number generators (QRNGs) harness the intrinsic randomness in measurement processes: the measurement outputs are truly random given the input state is a superposition of the eigenstates of the measurement operators. In the case of trusted devices, true randomness could be generated from a mixed state ρ so long as the system entangled with ρ is well protected. We propose a random number generation scheme based on measuring the quadrature fluctuations of a single mode thermal state using an optica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…Therefore, we conclude that case II, cw+pulse, may be the best choice for high-speed implementation of QRNG based on quantum phase noise (as demonstrated recently in [23,24]), while case I is suitable for simple and lowcost applications that may require slow rate QRNG only. Notice that high-speed implementation of case I is still possible by changing the scheme to a broadband source and a homodyne detection [25].…”
Section: (A) and 3(b)mentioning
confidence: 99%
“…Therefore, we conclude that case II, cw+pulse, may be the best choice for high-speed implementation of QRNG based on quantum phase noise (as demonstrated recently in [23,24]), while case I is suitable for simple and lowcost applications that may require slow rate QRNG only. Notice that high-speed implementation of case I is still possible by changing the scheme to a broadband source and a homodyne detection [25].…”
Section: (A) and 3(b)mentioning
confidence: 99%
“…This result has immediate implications for QRNGs based on continuous variables. QRNGs based on thermal light have been shown to offer enhanced min-entropy compared to QRNGs sampling vacuum, when using the same experimental resolution [30], but they either need to be operated as trusted QRNGs or used in applications where security of the random numbers is not relevant. Otherwise, eavesdropping attacks may reduce the performance of the thermal light QRNG such, that it does not offer any advantages compared to sampling vacuum.…”
Section: Discussionmentioning
confidence: 99%
“…In the following, we will denote the binned quadratures as X and P . Such QRNGs have already been realized using the vacuum [33] or thermal light [30] as input states. The random numbers determined this way are usually not distributed uniformly, so it is possible to perform additional randomness extraction [34] to create a compressed shorter string composed of independent identically distributed random numbers.…”
Section: The Continuous Variable Qrngmentioning
confidence: 99%
“…It is a common practice to apply a quantum random number generator (QRNG) [38,39] in prepare-and-measure QKD for state prepara- tion and/or measurement basis selection. As we have discussed in [34], while quantum randomness is ultimately connected to quantum superposition states, in the fully trusted device scenario, the quantum state received by the detector does not need to be a pure state. One illustrative example is the first generation QRNG, where electrons from a radioactive source such as 90 Sr are detected by a Geiger Mueller tube at random times [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…2) with vacuum state input is employed as a broadband thermal source. Previous studies have shown that the ASE noise generated by a fiber amplifier is thermal [22,[32][33][34]. To select out a single polarization mode, a fiber pigtailed polarizer (Pol in Fig.…”
Section: Experimental Setup and Noise Modelmentioning
confidence: 99%